Effect of Peer Education on safety Behaviors among Workers of renovation of structures and machines shop in Bandar Abbas Oil Refinery Company. - Sedigheh Aghamolaei; Teamur Rahmani; Mahdi Zare; Amin Ghanbarnejad (Iranian Association of Health Education and Health Promotion, 2014)
Background: An approach to control and prevent the occupational accidents is to make the workers aware of safe work practices and occupational hazards. This study aims to investigate the impact of peer education on safe behaviors among workers of renovation of structures and machines shop in Bandar Abbas Oil Refinery Company. Methods: In this interventional study, all 36 workers of Renovation of structures and machines shop of Bandar Abbas Oil Refinery Company were enrolled. Data were collected using demographic, knowledge, attitude, and behavior questionnaires. Questionnaires were completed at three stages including before the intervention and two and three months after the intervention. Behavior check lists were also completed before and three months after the educational intervention. Data were analyzed by paired t-test and repeated measures test using SPSS19 software. Results: The mean of knowledge scores before the intervention, two, and three months after the intervention were 33/5±6/83, 36/93±7/35, and 37/35±7/22 respectively. Significant increases in knowledge scores, two and three months after the intervention was observed (P<0/001). The mean of attitude scores before the intervention, two and three months after the intervention were 151/63±15/6, 153/5±13/58, and158/52±12/67, respectively. A significant increase was observed in attitude mean score three month after the intervention (P<0/01). A significant increase was observed in the mean of behavior scores three months after the educational intervention (6/83±2/75 vs. 8/27±1/74 P<0/001). Conclusion: The results of this study indicate that educational interventions using peers has been effective in promoting the workers safe practices. Therefore, peer education is recommended as an approach for promotion of safe work practices in the workplaces.